2014
DOI: 10.2298/pan1404415m
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of bank capital regulation: A cross-country analysis

Abstract: This paper identifies the main dimensions of capital regulation. We use survey data from 142 countries from the World Bank?s (2013) database covering various aspects of bank regulation. Using multiple explorative factor analysis, we identify two main dimensions of capital regulation: complexity of capital regulation and stringency of capital regulation. We show that even countries with a common legal and regulatory framework differ substantially in terms of capital regulation. For example, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Lehmann (2017) argued that a large proportion of NPLs ties up banks' capital and discourages credit supply. Marinč et al (2014) showed that the level of stringency of capital regulation varies substantially across the EU countries. Gandrud and Hallerberg (2014) showed that banks burdened by distressed and delinquent assets are unable to further supply loans to the economy.…”
Section: Literature Review Theoretical Framework and Hypothesis Devel...mentioning
confidence: 99%
“…Lehmann (2017) argued that a large proportion of NPLs ties up banks' capital and discourages credit supply. Marinč et al (2014) showed that the level of stringency of capital regulation varies substantially across the EU countries. Gandrud and Hallerberg (2014) showed that banks burdened by distressed and delinquent assets are unable to further supply loans to the economy.…”
Section: Literature Review Theoretical Framework and Hypothesis Devel...mentioning
confidence: 99%
“…Their lending response is the crucial response of banks to monetary policy. Marinc et al (2014) stated that, during the crisis period, the high quality of the banking financing strategy and the prevalent government support were crucial for continuous bank lending. He concluded that bank capital and the provision of high-quality services are in fact the competitive strength of a bank in times of crisis.…”
Section: Theoretical Frameworkmentioning
confidence: 99%